2017
DOI: 10.1111/jfs.12409
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Thymus capitatus and Thymus algeriensis essential oils against four food‐borne pathogens inoculated in minced beef meat

Abstract: The antibacterial activity of the essential oils extracted from Thymus capitatus and Thymus algeriensis was studied against Escherichia coli, Salmonella typhimurium, Staphylococcus aureus, and Pseudomonas aeruginosa. In this study, the disk method showed that T. capitatus EO has a strong antibacterial effect, whereas T. algeriensis EO showed a moderate activity. In addition, the inhibitory effect of both EOs was evaluated against four pathogenic strains inoculated experimentally [vol/wt]), the bactericidal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…e strains of L. monocytogenes (ATCC 19118) were cultivated in PALCAM Listeria agar (Biokar Diagnostics), S. aureus (ATCC 25923) in Baird-Parker (Biokar Diagnostics), E. coli (ATCC 25922) in Mac Conkey Sorbitol (Biolife), S. typhimurium (ATCC 1402) in Hektoen (Biolife), and P. aeruginosa (ATCC 27853) in Pseudomonas agar F (King's Medium B) (Biolife), at 37°C. Working cultures were prepared by adding a loopful of each test bacterium to 5 ml of Luria-Bertani Medium (LB) (Oxoid Ltd., UK) and then incubated at 37°C for 18 h [20].…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 99%
“…e strains of L. monocytogenes (ATCC 19118) were cultivated in PALCAM Listeria agar (Biokar Diagnostics), S. aureus (ATCC 25923) in Baird-Parker (Biokar Diagnostics), E. coli (ATCC 25922) in Mac Conkey Sorbitol (Biolife), S. typhimurium (ATCC 1402) in Hektoen (Biolife), and P. aeruginosa (ATCC 27853) in Pseudomonas agar F (King's Medium B) (Biolife), at 37°C. Working cultures were prepared by adding a loopful of each test bacterium to 5 ml of Luria-Bertani Medium (LB) (Oxoid Ltd., UK) and then incubated at 37°C for 18 h [20].…”
Section: Microorganisms and Growth Conditionsmentioning
confidence: 99%
“…The inhibition zones observed in another study of antibacterial activity of the T. algeriensis essential oil were 13 mm against P. aeruginosa, 12 mm against S. aureus, 28 mm against E. coli and 20 mm against S. typhimurium. (Jayari et al, 2018).…”
Section: Assay For the Antibacterial Potentialmentioning
confidence: 99%
“…For many research groups, the inhibitory effect of T. algeriensis essential oil could be resulted from its composition of linalool and camphor, known to have excellent antibacterial properties or could be related to monoterpene hydrocarbons and oxygenated monoterpenes which are able to affect cell integrity, conducting to both the inhibition of the respiration and an alteration of the permeability. (Jayari et al, 2018). Kabouche et al (2005), reported that very high antibacterial potential (inhibition zones) of the essential oils of Thymus numidicus from 34 to 66 mm and 26-54 mm with Thymus fontanesii, antagonistic toward E. aerogenes, E. coli, K. pneumoniae, P. aeruginosa, S. aureus, but S. typhimurium was not affected.…”
Section: Assay For the Antibacterial Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for an essential oil to maintain its high antimicrobial activity when added to foods, its concentration must normally be greater than the concentration required for antimicrobial activity in vitro. Jayasena & Jo [15], in a review study, show that, in most antimicrobial evaluations of essential oils in meat products, only one essential oil is used and usually at high concentration, as shown in the study with ground beef, that was necessary more than 1% of essential oil of two species of Thymusto inhibit the growth of E. coli, Salmonella thyphimurium and Staphylococcus aureus [16]. This often leads to decharacterization of the food products and therefore to difficulty in using essential oils as food…”
Section: Introductionmentioning
confidence: 99%